Dietary Eucommia ulmoides Extracts Improve Pathogen Resistance in Large Yellow Croaker Juveniles by Modulating Immune-Related Pathways and Gut Microbiota - Jianjun Xie; Yexiang Xu; Gengshen Wang; Min Jiang; Wei Wang; Dongxu Zhang; Wenjun Xu (Fishes, 2026)
Various immunostimulants have been employed to enhance the efficacy of aquaculture. However, the mechanisms by which Eucommia ulmoides extracts affect the pathogen resistance of large yellow croakers remain to be elucidated. In this study, a multi-omics investigation was conducted to investigate the potential for enhancing pathogen resistance and to elucidate the underlying mechanisms of Eucommia ulmoides extracts on large yellow croaker juveniles. It revealed that the survival rate of the large yellow croaker juveniles was significantly enhanced (approximately doubled) by oral extracts of Eucommia ulmoides in the context of pathogen invasion. Examining the transcriptome of the liver revealed that Eucommia ulmoides extracts have the capacity to activate the class I MHC pathway for antigen processing, including genes for HSP70, HSP90, CALR, TAPBP, MHCI, and TCR. This, in turn, facilitates the phagocytosis of pathogens by the immune system. Furthermore, the alpha-diversity of the large yellow croaker juveniles’ gut microbiota was increased by the Eucommia ulmoides extracts, maintaining the stability of the gut microbiota and reducing the ratio of pathogens (Burkholderia cenocepacia and Streptococcus iniae) following a pathogen challenge. The application of correlation analyses indicated that a reduction in pathogens was closely associated with variations in whole gut microbiota.